Does Characteristics-Media-Environmental Performance Trilogy Predict Carbon Emissions Disclosure by Sharia Companies? - Windy Fatmawati; Ria Anisatus Sholihah; Ade Gunawan (LPPM ISNJ Bengkalis, 2026)
Global carbon emissions, according to the Global Energy Review by the International Energy Agency, increase dramatically to 37.8 gigatons (Gt) by 2024. In Indonesia, energy companies dominate 56% of carbon emissions and contribute 37% from the basic-material sector. This condition is a result of voluntary disclosure and the ineffectiveness of the obligation of sustainability disclosure standards. Therefore, this study seeks to examine the influence of company characteristics and media exposure on carbon emission disclosure with environmental performance moderation variables. The research adopts a quantitative method. A sample of 31 companies in the energy and basic-material sectors listed on the Indonesian Sharia Stock Index from 2021 to 2024. Data collection is sourced from annual and sustainability reports and other secondary sources. The researcher used Eviews 12 software in the form of panel data regression analysis and moderated regression analysis (MRA). This study found that the characteristics of companies in the form of company size partially have a significant positive effect on carbon emission disclosure. Profitability and leverage partially have a significant negative effect on carbon emissions disclosure. Meanwhile, media exposure has no significant effect on the disclosure of carbon emissions. Environmental performance variables are able to moderate the influence of media exposure on carbon emission disclosure. However, it is not able to moderate the influence of company characteristics in the form of company size, profitability, and leverage on carbon emission disclosure.